E-Learning YOUTH4OSH Educcation: Analysis of Differences Safety Behavior During Practicum For State Vocational School Students - Maulida, Fakhria; Denny, Hanifa; Setyaningsih, Yuliani (Universitas Negeri Semarang, 2025)
Background: Education Youth4OSH e-learning is one of the ILO's efforts to reduce the high number of young worker accidents. This study aims to determine differences in knowledge, attitudes, and practices of safety behavior during practicum before and after being given education through Youth4OSH e-learning. Methods: This research used a non-equivalent control group quasi-experimental study design, with a purposive sampling technique and a sample of 30 students in the control group and 31 students in the treatment group. Interventions involve OSH education through Youth4OSH e-learning, which is provided three times over three weeks. Data analysis utilized the Wilcoxon signed-rank test and Mann-Whitney U Test. Results: The results of the Wilcoxon signed-rank test showed that there was an increase in the scores of knowledge (p= 0.000), attitudes (p= 0.000), and practices (p= 0.000) in the treatment group. Furthermore, differences in enhancement scores of knowledge, attitudes, and practices between the treatment group and the control group are observed using the Mann-Whitney U test, which showed a p-value of 0.000 (p<0.05). Conclusions: There were differences in knowledge, attitudes, and practices of safety behavior before and after receiving Youth4OSH e-learning education.